Efficient water treatment achieved in recirculating aquaculture system using woodchip denitrification and slow sand filtration - Lindholm-Lehto, Petra Camilla; Pulkkinen, Jani Tapio; Kiuru, Tapio; Koskela, Juha; Vielma, Jouni (Springer, 2021)
For a recirculating aquaculture system (RAS), a passive water treatment system was designed for efficient discharge nutrient removal and water reuse in RAS production. Denitrification in a woodchip bioreactor filled with birch wood (Betula pendula) followed by sand filtration was introduced into a side-loop of an experimental RAS rearing rainbow trout (Oncorhynchus mykiss). Denitrification efficiency remained high (96%) throughout the experiment and reached a nitrogen removal rate of 15 g NO3-N m−3 per day. Sand filtration was used to remove dissolved and particulate matter and improve water quality before being returned to water circulation. To ensure the absence of harmful substances in the system, heavy metals were quantified. Additionally, off-flavor-inducing compounds were quantified in the circulating water and in fish flesh. Significantly higher concentrations of geosmin (GSM) (p<0.05) were observed in the controls compared to side-looped systems, but a similar effect was not observed in the case of 2-methylisoborneol (MIB). Among heavy metals, concentrations of Co (30 μg L−1), Ni (40 μg L−1), and Pb (140 μg L−1) decreased to below 10 μg L−1 in the side-loop water after the start-up of the system. Only low concentrations of Cu (5–30 μg L−1) were found in the rearing tank water, in both the side-loop and controls. The results indicated that this type of process design is suitable for safely producing fish of high quality.
Keywords: Denitrification; Heavy metals; Off-flavors; Particulate matter removal; Rainbow trout; Recirculating aquaculture system (RAS)